Long‐term efficacy and safety of adjunctive ethanol infusion into the vein of Marshall during catheter ablation for nonparoxysmal atrial fibrillation - Liu, Chih‐Min; Lo, Li‐Wei; Lin, Yenn‐Jiang; Lin, Chin‐Yu; Chang, Shih‐Lin; Chung, Fa‐Po; Chao, Tze‐Fan; Hu, Yu‐Feng; Tuan, Ta‐Chuan; Liao, Jo‐Nan; Chen, Yun‐Yu; Kuo, Ling; et al. (Journal of cardiovascular electrophysiology, 2019)
Introduction We aimed to clarify the effect of vein of Marshall (VOM) ethanol infusion for treating VOM triggers and/or mitral flutter after first‐attempt endocardial ablation in patients with nonparoxysmal atrial fibrillation (AF). Methods and Results Of the 254 consecutive patients (age, 56 ± 10 years; 221 male) undergoing catheter ablation for drug‐refractory nonparoxysmal AF, 32 (12.6%) received VOM ethanol infusion. The patients were stratified into group 1 (pulmonary vein isolation [PVI], substrate modification, VOM ethanol infusion), group 2 (PVI, substrate modification), and group 3 (PVI alone). Propensity‐matched analysis (N = 128) of long‐term outcomes (3.9 ± 0.5 years) revealed a higher AF recurrence risk in group 2 (hazard ratio [HR], 4.17; 95% confidence interval [95% CI], 1.63‐10.69; P = .003) and group 3 (HR, 1.82; 95% CI, 1.09‐3.04; P = .021) than in group 1, as well as a higher atrial arrhythmia recurrence risk in group 2 than in group 1 (HR, 2.42; 95% CI, 1.16‐5.03; P = .018). A higher procedural termination rate was observed in group 1 than groups 2 and 3 (41.7% vs 17.2% vs 18.8%; P = .042). On multivariate analysis, VOM ethanol injection was an independent predictor of freedom from recurrence of AF (HR, 0.20; 95% CI, 0.08‐0.52; P = .001) and atrial arrhythmia (HR, 0.35; 95% CI, 0.17‐0.74; P = .005), whereas a left atrial diameter >45 mm and hypertension were independent risk factors for recurrence. Periprocedural complications rates were comparable among the groups. Conclusion Adjunctive VOM ethanol infusion is effective and safe for treating nonparoxysmal AF in patients with VOM triggers and/or refractory mitral flutter, providing good long‐term freedom from AF and atrial arrhythmia.